The Effect of Entrepreneurial Orientation on SMEs’ Performance: Market Orientation as a Mediating Variable - Yissa Hassen Kassim (Journal of Research and Innovation, 2023)
The study investigated the effect of Entrepreneurial Orientation (EO) dimensions and performance: Market Orientation (MO) as a mediating role in the case of SMEs in Amhara Regional State of Ethiopia. A Structural Equation Modelling (SEM) was employed to analyze and test hypothesis. The result indicates that the direct effect of autonomy, innovativeness, Proactiveness & competitive aggressiveness dimensions of EO are significant. In addition, MO partially mediates autonomy, innovativeness, Proactiveness and competitive aggressiveness dimensions of EO and SMEs’ performance linkages. Therefore, with MO, EO dimensions will give superior SMEs’ performance.  However, risk taking has no significant effect on the SMEs performance as well as risk taking -performance relationship was not found to be mediated by MO. Thus, the higher SMEs are entrepreneurially oriented, the more they are willing to be market oriented that intern positively affects the performance of SMEs. The findings reveal owner/managers of SMEs needs to be more entrepreneurially oriented to create a well-built MO environment that enables them intensively competitive in the fast-changing market environment and to improve their performance. This study contributes to the almost wholly overlooked research about east African SMEs’ strategic orientation and performance linkages. Therefore, the study can provide an opportunity to expand the research on other sectors such as construction, agriculture, hotel & tourism and trade business enterprises.